Investigating students’ favourite themes of history fieldwork in the integrated curriculum for secondary schools, Malaysia - Salleh, Mohamad Johdi (Centre for Promoting Ideas, USA, 2013)
The study is essentially an exploratory survey, which sets out to obtain some concrete information on the students’ knowledge and understanding of, and attitudes towards, the favourite themes of fieldwork approaches to history in the Integrated Curriculum for Secondary Schools (ICSS), Malaysia. The researcher employed the ‘stratified-random sampling’ method and selected two states in Malaysia, namely Perak and Terengganu, involving 400 students from each state. As an addition, the researcher conducted interviews with forty conveniently selected respondents. The responses were presented in the form of frequency and percentage. The results of the study show that the top three favourite themes selected by students in history fieldwork were ‘building’ with the score of 242 (30.3%), followed by ‘family’ 121 (15.1%) and ‘public figures’ with 101 (12.6%) responses. On the other hand, the least popular theme among the students was ‘occupation’ with 22 (2.8%) responses. The perceptions of students on these three themes were presented in the interview section. It is hoped that the study would raise concern, awareness and benefit to all involved in the teaching and learning of fieldwork approaches to history, especially the Standard School Curriculum of Malaysia beginning from year 2011 towards the realisation of Vision 2020, 1-Malaysia, and, Malaysia Education Blue-Print 2013-2025.